Pengembangan Media Ular Tangga Berbasis Kooperatif Tipe Teams Games Tournament (TGT) Untuk Melatihkan Aktivitas Belajar Siswa - Rani Novriza Putri; Agusminarti Agusminarti; Hadi Purwanto (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2026)
Learning media is a tool that can be used to help students learn better and more efficiently. The media used in SMP Negeri 23 Pekanbaru is a teacher-centered picture/poster media so that students quickly get bored, and because of the limited media from the school. Most students prefer learning that involves them directly such as the element of games. The learning models used are discovery, PBL, and lecture models, and student learning activities are still lacking or less active in science learning. The purpose of this study is to develop learning media in the form of a cooperative-based snakes and ladders game with the Teams Games Tournament (TGT) type which aims to train student learning activities. The research method used is Research and Development (R&D) by implementing the ADDIE model which consists of five stages, namely Analyze, Design, Development, Implement, and Evaluation. Based on the validation results obtained, media experts were 94% with very feasible criteria, material experts were 92% with very feasible criteria, teachers gave a practicality assessment of 95% with very practical criteria, and students' responses were 85% with very interested criteria. This shows that the snakes and ladders media based on Teams Games Tournament (TGT) is very reasonable, very practical to use, and very interesting for students during the learning process. The results of observations on all student learning activities showed that 79% got a good interpretation.